2020
DOI: 10.3892/etm.2020.8444
|View full text |Cite
|
Sign up to set email alerts
|

Effect of five dental pulp capping agents on cell proliferation, viability, apoptosis and mineralization of human dental pulp cells

Abstract: The aim of the present study was to investigate the effect of calcium hydroxide [Ca(OH) 2 ], mineral trioxide aggregate (MTA), iRoot BP, platelet-rich fibrin (PRF) and concentrated growth factors (CGF) on the proliferation, viability, apoptosis and mineralization of human dental pulp cells (HDPCs). HDPCs were treated with Ca(OH) 2 , MTA, iRoot BP, PRF and CGF exudates. Cell viability, apoptosis, proliferation, cell cycle and alkaline phosphatase (ALP) activity were evaluated in vitro. PRF significantly increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…In this study, cellular analysis was performed using the eluates from both tested materials. According to the International Standard ISO 10993-12 Biological Evaluation of Medical Devices [17], we obtained eluates of the materials, and hPDLSCs were treated with different eluates, similar to previously reported studies [18][19][20]. The tests performed on those eluates allowed both qualitative and quantitative assessment of biocompatibility.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, cellular analysis was performed using the eluates from both tested materials. According to the International Standard ISO 10993-12 Biological Evaluation of Medical Devices [17], we obtained eluates of the materials, and hPDLSCs were treated with different eluates, similar to previously reported studies [18][19][20]. The tests performed on those eluates allowed both qualitative and quantitative assessment of biocompatibility.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies have shown that a combination of Wnt3a, BMP7, and collagen gel delivered into the root canal of mini-pigs yielded pulp-dentin-like structures with obvious dentinal tubules (He et al, 2019). Furthermore, many bloodderived scaffold materials containing rich growth factors are used in clinical pulp therapy, such as platelet-rich plasma (PRP), concentrated growth factors, and platelet-rich fibrin, and showed a much better influence on cell proliferation, viability, apoptosis, and mineralization of human dental pulp cells than traditional materials such as Ca(OH) 2 , mineral trioxide aggregate, and iRoot BP (Dou et al, 2020). Moreover, Jadhav et al (2012) proved that PRP showed a better treatment effect in periapical healing, apical closure, and dentinal wall thickening compared to blood clots in regenerative endodontic tissue.…”
Section: Cytokines Combined With Scaffold Transplantationmentioning
confidence: 99%
“…It is used for pulp capping, root perforation, retrograde root-end filling, and the obturation. 74 Review Article SMJ Biodentine. comprises tricalcium silicate, dicalcium silicate, calcium carbonate, calcium oxide, and zirconium oxide (radiopaque).…”
Section: Tri-calcium Silicate Based Materialsmentioning
confidence: 99%